Factors Associated with the Intention-to-Leave Among Fast Food Workers in Three Selected Cities, Malaysia - Ahmad, Azlinzuraini (2001)
Fast food workers' competence is important in ensuring fast food efficient services. High employee turnover could inhibit the growth of the fast food industry. It was reported that 'others' sector in the 1999 Malaysian Economic Report, which included restaurants contributed 23.1% of new job vacancies annually. Therefore, it is of vital importance for managers and employers to identify and understand the factors which enhance the intention-to-leave among workers in the fast food sector. The general objective of this study is to identify and analyse factors contributing to the intention-to-leave among Malaysian fast food workers. Specifically, it aims to identify the individual characteristics, the level of job satisfaction, the level of respondents' knowledge about alternative job opportunities and the respondents' levels of intention-to-leave; and to determine the relationships of research variables, namely the individual characteristics, alternative job opportunities, job satisfaction with the intention-to-leave. A survey was conducted in Kuala Lumpur, Johor Bahru and Penang by using a validated instrument (questionnaire). The questionnaire comprised of three major parts which consisted of the profile of respondents, job satisfaction and intention-to-leave. A slightly modified version of the 72 items of Job Descriptive Index (JDI) and the 4-questions from Hunt et al. (1981) were used as measurements in the questionnaires. A total of 284 valid responses was obtained. Frequencies, descriptive and regression analysis were used in analysing the data. The findings of this study reveals that the individual characteristics, alternative job opportunities, and job satisfaction were important factors in causing the intention-to-leave to rise among the respondents. The results also indicates that the factors job satisfaction, full-time workers, respondents' salaries, and higher salary offered by other industries were highly significant. Based on the findings, the full-time workers tend to stay longer on their jobs as compared to part-time workers. Therefore, to reduce the rate of turnover, the industry should take in more full-time workers and perhaps provides them better salary and benefits. The industry should also conduct job analysis and employees' appraisals frequently to monitor job satisfaction levels of the workers. So that, appropriate and timely actions can be taken to reduce the turnover rate.